Nanostructured Particles for Controlled Polymer Release in Enhanced Oil Recovery. Issue 9 (3rd May 2016) - Tamsilian, Yousef; S. A., Ahmad Ramazani; Shaban, Masoom; Ayatollahi, Shahab; de la Cal, Jose C.; Sheng, James J.; Tomovska, Radmila
Abstract: With the decline in oil discoveries over recent decades, it is believed that enhanced oil recovery (EOR) technologies will play a key role to meet energy demand in the coming years. Polymer flooding is used commonly worldwide as an EOR process. In this work, we propose the synthesis of protected polyacrylamide (PAM) nanoparticles (PPNs) with a hydrophobic polystyrene (PSt) shell by one‐pot two‐step inverse emulsion polymerization, in which the PSt shell was created by surface polymerization. The shell protects the active PAM chains from premature degradation caused by the harsh environment in the reservoirs, controls the release of the chains as rheological modifiers, and additionally, it provides the chains with prolonged stability. The time‐dependent release of the PPNs promotes the effectiveness of the PPNs as viscosity modifiers, as the maximum viscosity enhancement is achieved at longer residence times in the reservoirs. This can be up to 30 days, and the released polymer maintained its activity. Under conditions of high salinity (total dissolved solids=178 082 mg L −1 ), temperatures up to 90 °C, and shear rates up to 1000 s −1, PPNs have shown superior properties, such as elastic modulus, shear rate behavior, viscosity loss, and sand adsorption over PAM, whereas the areal sweep efficiency of PPNs is similar to that of PAM and higher than that of conventional water flooding. All of this makes PPNs promising candidates for polymer‐enhanced oil recovery. Abstract : To the well in a shell : The synthesis of protected polyacrylamide (PAM) nanoparticles (PPNs) with a hydrophobic polystyrene shell by one‐pot two‐step inverse emulsion polymerization is reported. The shell protects the active PAM chains from premature degradation caused by the harsh environment in reservoirs, controls their release as rheological modifiers, and provides the chains with prolonged stability.